Molecular association and relaxation phenomena in water solutions of organic liquids examined by photoacoustic and ultrasonic methods - Linde, B.B.J.; Sikorska, A.; Śliwiński, A.; Żwirbla, W. (Archives of Acoustics, 2006)
Examinations of water solutions of organic liquids carried out recently using both photoacoustic and ultrasonic methods have shown possibility of wider interpretation of the phenomena of clathrate structures creation (quasi stable associates) and relaxation processes taking place in water – glycols solutions. The discussion of the obtained results for mentioned above phenomena is presented. This allowed us for the comparison and common interpretation of the experimental results.